Metal- and additive-free oxygen-atom transfer reaction: an efficient and chemoselective oxidation of sulfides to sulfoxides with cyclic diacyl peroxides. Issue 12 (7th March 2017) - Gan, Shaoyan; Yin, Junjie; Yao, Yuan; Liu, Yang; Chang, Denghu; Zhu, Dan; Shi, Lei
Abstract : Metal- and additive-free sulfoxidation was developed using cyclic diacyl peroxides as oxygen sources and a single two-electron transfer mechanism was suggested. Abstract : Metal- and additive-free oxidation of a series of sulfides/thioketones has been achieved using cyclic diacyl peroxides as mild oxygen sources. This protocol features simple manipulation, high chemo- and diastereoselectivity, and a broad substrate scope (up to 42 examples), tolerates many common functional groups, and is scalable and applicable to the late-stage sulfoxidation strategy. A preliminary mechanistic study by quantum mechanical calculations suggests that a single two-electron transfer process is energetically more favorable, and indicates the reactivity of cyclic diacyl peroxides distinct from conventional acyclic acyl peroxides.